Student Character Building through Scouting Activities in Elementary School - Zulfa S, Rama Viona; Ain, Siti Quratul (JMKSP (Jurnal Manajemen, Kepemimpinan, dan Supervisi Pendidikan), 2025)
This research aims to analyze student character building through scouting activities at SDN 170 Pekanbaru. Data sources came from scout coaches, students, and documents related to activities. Data collection techniques include interviews, observations, and documentation studies. Data analysis was carried out descriptively qualitative. The results showed that the implementation of scout activities was carried out regularly with various interesting and participatory methods, and the material of scout activities included aspects of general skills, special skills, and the development of Dasa Dharma values. Furthermore, this study identifies the character values formed, namely: the character value of the relationship with God is reflected in prayer activities and gratitude; the character value of the relationship with oneself is seen in the independence, responsibility, and discipline of students; the character value of the relationship with others appears in the attitude of mutual cooperation, tolerance, and social care; and the character value of the relationship with the environment is shown through cleaning activities and love of nature. In conclusion, scouting activities at SDN 170 Pekanbaru are effective in shaping various positive character values in students.